Partisipasi Pembelajaran Siswa Dalam Pembelajaran Dengan Classroom Rules - Noviyanti, Ayu Kristiana; Setyaningtyas, Eunice Widyanti (LPPM Undiksha, 2017)
This study aims to: (1) Determine the effect of applying classroom rules in participation in teaching students in grades 5 (2) Determine the level of success of the effect of applying classroom rules in participation in teaching students in grades 5 Classroom rules are a set of rules which help organize learning activities, not just a routine or habit but in practice is also based on a standard that will have a positive impact on student behavior both in learning and everyday attitudes. This type of research is experimental research with research design Quasi Experimental Design. Instruments data collection using questionnaires, observations and interviews. Hypothesis testing using t-test and two independent samples t-test two different paired sample with SPSS 16.0. The results showed that: (1) the results of pre-test and post-test participation learning experimental class increased after applying classroom rules is higher than pre-test participation study before applying classroom rules with an average participation of learning by 52 904 and the average after applying classroom learning participation rules amounted to 55 761; (2) Participation of higher learning experimental class of classes controls (t = 2.342> ttabel 5% = 2,021). Thus the application of classroom rules affect the increased participation of student learning. Application of the rules Clasroom done optimally will affect the formation of character and the effect on student achievement.